Multiple osteochondromas in a 16th–19th century individual from Setúbal (Portugal) - Antunes-Ferreira, Nathalie (2017)
An archaeological survey at the church of Nossa Senhora da Anunciada (Setúbal, Portugal) uncovered the remains of 92 individuals. Historical and archaeological data suggest that the inhumations occurred between 1531 and 1839. The present work reports the pathological features of a mature male individual exhibiting multiple osseous bony projections and bone deformity, mainly affecting the metaphyseal and adjacent diaphyseal regions of the long bones. The macroscopic and the radiological analyses of the lesions suggest multiple osteochondromas as the most probable diagnosis. This is the first archaeological case of this disease known on the Portuguese territory and in southern Europe.